2012
DOI: 10.1007/s10495-011-0696-8
|View full text |Cite
|
Sign up to set email alerts
|

GAS1 induces cell death through an intrinsic apoptotic pathway

Abstract: Growth Arrest Specific 1 (GAS1) is a protein expressed when cells are arrested and during development. When ectopically expressed, GAS1 induces cell arrest and apoptosis of different cell lines, and we have previously demonstrated that the apoptotic process set off by GAS1 is caused by its capacity inhibiting the GDNF-mediated intracellular survival signaling. In the present work, we have dissected the molecular pathway leading to cell death. We employed the SH-SY5Y human neuroblastoma cell line that expresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 36 publications
(32 reference statements)
4
38
0
Order By: Relevance
“…It is interesting that the effects of GAS1 in inducing apoptosis are independent of the SHH pathway (DominguezMonzon et al 2009;Dominguez-Monzon et al 2011;Zarco et al 2012). Previous experiments have shown that the overexpression of GAS1 can potentiate SHH signaling and that GAS1 inactivation decreases SHH signaling in the neural tube (Tenzen et al 2006;Allen, Tenzen, and McMahon 2007;Martinelli and Fan 2007;Allen et al 2011;Izzi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that the effects of GAS1 in inducing apoptosis are independent of the SHH pathway (DominguezMonzon et al 2009;Dominguez-Monzon et al 2011;Zarco et al 2012). Previous experiments have shown that the overexpression of GAS1 can potentiate SHH signaling and that GAS1 inactivation decreases SHH signaling in the neural tube (Tenzen et al 2006;Allen, Tenzen, and McMahon 2007;Martinelli and Fan 2007;Allen et al 2011;Izzi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[89,96,[102][103][104] Ptc and Gli are highly expressed in gliomas and are considered oncogenes. [105,106] Therefore this would suggest that Gas1 could enhance the effect of Shh, inducing the proliferation of glioma and neuroblastoma cells, however we showed that Gas1 inhibits cell proliferation of glioma cells even in the presence of the Shh molecular machinery, [107,108] which suggest that in tumors Gas1 inhibits the GDNF signaling pathway.…”
Section: Gas1 Promotes Shh Signalingmentioning
confidence: 81%
“…[114] In neuroblastoma and glioma cells, Gas1 blocks cell cycle progression, inhibits proliferation and induces cell death by inhibiting the GDNF/AKT pathway. [107,108,115,116] We showed that Gas1 prevents the phosphorylation of Ret Tyr1062 and reduces the activation of AKT [ Figure 1]. This leads to the translocation of BAD to the mitochondria and the release of cytochrome-C to the cytosol which in turn induces the activation of Caspases 9 and 3.…”
Section: Gas1 Inhibits the Signaling Induced By Gdnf And Arteminmentioning
confidence: 99%
See 2 more Smart Citations